2015
DOI: 10.1111/ane.12373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunctive zonisamide treatment on weight and body mass index in children with partial epilepsy

Abstract: Approximately one-third of children treated with zonisamide experienced ≥ 5% weight loss. Weight loss was most apparent in children with high baseline BMI values and did not appear to be associated with any consistent effects on growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…It has been reported that 24% (99% CI: 2-46%) of ZNS-treated patients develop weight loss, and losses may reach up to 8 kg [63,64]. In children, weight loss ≥5% has been observed in approximately 35% [65]. ZNS has been studied as an antiobesity drug but as yet it has not become an established treatment [24,66].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…It has been reported that 24% (99% CI: 2-46%) of ZNS-treated patients develop weight loss, and losses may reach up to 8 kg [63,64]. In children, weight loss ≥5% has been observed in approximately 35% [65]. ZNS has been studied as an antiobesity drug but as yet it has not become an established treatment [24,66].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Confounding conditions included congenital malformations, 23 brain injury, 24 seizure, 25 technology dependence, cancer, 21 eosinophilic esophagitis 26 or milk protein…”
Section: Confounding Health Conditionsmentioning
confidence: 99%
“…The addition of zonisamide to treating a 15-year-old obese male admitted to the hospital for depression and anxiety symptoms resulted in appetite suppression by acting on the hypothalamus, weight loss and normalization of his triglyceride levels [ 101 ]. In addition, results from clinical trials investigating the effect of zonisamide as add-on therapy in children suffering from partial seizures on weight reduction showed that about 35.8% of the treated patients experienced significant weight reduction (≥5% reduction of body weight) [ 102 ].…”
Section: Treatmentmentioning
confidence: 99%